“Can do” vs. “do do” in older adults: a cross-sectional analysis of sensor-derived physical activity patterns - Adams, Michael; Carrascosa, Lara; Jansen, Carl-Philipp; Ritter, Yvonne; Schwenk, Michael (Sensors, 2023)
(1) Background: Identifying groups with a misaligned physical capacity (PC) and physical activity (PA) is potentially relevant for health promotion. Although an important health determinant, deeper knowledge of underlying walking behavior patterns in older adults is currently missing. We aim to identify specific PA signatures of misaligned groups and determine PA variables discriminating between groups. (2) Methods: In total, 294 community-dwelling older adults (≥70 years) were divided into four quadrants based on thresholds for PA (≥ or <5000 steps/day) and PC (≤ or >12 s, Timed Up and Go test). Kruskal-Wallis and effect sizes were calculated to compare quadrants’ PA variables and to determine the discriminative power of PA parameters on walking duration, frequency, and intensity. (3) Results: We identified quadrant-specific PA signatures. Compared with “can do-do do”, the “cannot do-do do” group performs shorter continuous and lower-intensity walks; the “can do-do not do” group takes fewer steps and walks with less intensity. The “cannot do-do not do” group presents lower values in all PA variables. “Walking duration greater or equal 3 METs” was the strongest discriminative PA variable. (4) Conclusion: We provide distinct PA signatures for four clinically different groups of older adults. Walking intensity is most useful to distinguish community-dwelling older adults, which is relevant for developing improved customized health promotion interventions.
Gesehen am 29.03.2023